Results of using cell technologies for creation of new barley varieties resistant against aluminum toxicity and drought - O. N. Shupletsova; I. N. Shchennikova (Вавиловский журнал генетики и селекции, 2016)
Results of a study of economically valuable parameters of barley regenerant lines obtained by cell selection on selective media with aluminum, hydrogen ions and polyethylene glycol are presented. Genotypes superior to the initial variety and standard variety have been identified under laboratory conditions: root length index (regenerants: 0.9–1.2 %; standard: 0.8 %) and drought resistance (regenerants: 17.8–45.2 %; standard: 8.5 %); productive parameters under growth chamber conditions (12 % increase in germination ability, 21 % increase in productive plant stand, 2.3- fold increase in grain number per ear, 1.5-fold increase in weight of grains per plant). The parameter ”weight of grains per plant” correlates with the level of alkalization of the rhizosphere zone of the investigated plants under stressful conditions in growth chamber experiments (r = 0.908). Regenerant pants are typically much less affected by phytopathogenic fungi. The genotypes screened in selective systems in vitro had advantages over the initial varieties and standard varieties in productivity, especially under provocative conditions of acid soils and moisture deficit in 2010. As a result of field tests, the genotypes of regenerant origin were identified that had consistently shown a 10.0–43.2 % higher productivity than the standard variety over several years. The proportion of varieties regenerated at the stage of competitive variety trials increased from 8.3 % (2006) to 32.4 % (2014). The varieties regenerated with high combining ability are used as the parental forms in crosses. New barley varieties Forward and Bionik have been developed on the basis of regenerant lines 917-01 and 496-07. Under edaphic stress (pH 3.8–4.5; Аl3+ 0.5–9.6 mg/100 g soil), Forward has productivity up to 5.5 t/ha and Bionik, 6.6 t/ha; which is 113–128 % higher than the standard.